Termination of Employment for Urgent Reasons: Issues on Worker Protection - Fauzan (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Termination of Employment for urgent reasons has made it easier for Employers to carry out layoffs without going through the Industrial Relations Dispute Resolution Institution process in accordance with the Job Creation Law in conjunction with Article 52 paragraph (2) of Government Regulation No. 35 of 2021. The provisions for layoffs for urgent reasons have experienced ups and downs, after being prohibited by the Constitutional Court Decision Number 012/PUU-I/2003 and then revived by the Job Creation Law in conjunction with Government Regulation No. 35 of 2021. In law enforcement, decisions of the Industrial Court also pave the way for layoffs for urgent reasons. This research uses a normative juridical approach, conducted to find out the history of regulations for layoffs for urgent reasons starting from those regulated in the Civil Code, Law No. 57 of 1957 in conjunction with Law No. 12 of 1964, Law No. 13 of 2003, Constitutional Court Decision No. 12/PUU-I/2003 and the Job Creation Law in conjunction with Government Regulation No. 35 of 2021 and to determine the application of the law by Industrial Relations Court judges in disputes over termination of employment for urgent reasons. The research findings regarding the provisions on termination of employment for urgent reasons as stipulated in the current provisions and the application of the law by Industrial Relations Court judges do not consider the principle of maintaining employment relationships to the extent possible.